A Comparative Analysis between Paninian and Tesni`ere’s Dependency Formalisms with Specific Reference to Annotating Karta - Pitambar Behera (International Journal of Advanced Science and Technology, 2020)
Paninian Dependency (PD) framework takes into consideration both the syntactic and semantic aspects whereas the Tesni`ere’s Dependency (TD[1]) formalism is oriented more towards the semantic aspect for annotation. On one hand, the former is modeled upon the Paninian model of Sanskrit grammar. On the other hand, the latter is based on Tesni`ere’s initial experimentation in French; later universalized with the advent of Natural Language Processing and inspires Universal Dependency (UD) formalism. Researchers like Kiparsky and Staal in 1969 and Bharati and others in 1995 have emphasized on the point that the PD formalism is accommodative of Indian languages drawing empirical observations from Hindi-Urdu. Therefore, it is hypothesized that PD will be more suitable and accommodative of Odia language as well. For that said purpose, a comparative analysis between the Paninian and Universal Dependency Formalisms has been conducted to figure out which formalism works better for Odia with special reference to the annotation of the karta ‘k1’ dependency relation.